(untitled) (Brazilian Journal of Health Research, 2022)
Introduction: The pharmacist is responsible for the pharmaceutical indication as a professional act in which he is responsible for the selection of an over-the-counter medication. Objectives: The objective of this study was to know the attitude of community pharmacists regarding the practice of pharmaceutical counseling. Methods: This is a descriptive and cross-sectional study in which all pharmacist for community pharmacies in the metropolitan region of Belo Horizonte in the state of Minas Gerais, Brazil (n = 1,624) were invited via e-mail. For data collection (period from October to December 2017), a questionnaire available on the Google Docs® platform, containing a multiple-choice question related to the conduct of medication indication was used. Results: Responses were received from 108 pharmacists, of which 88.0 % stated that they pharmaceutical indication, 7.4 % self-declared never to indicate medication and 4.6 % chose not to answer. Among the pharmacists who indicate medication, 28.4 % described inappropriate conduct in medication indications as suggesting the use of medication that were not over the counter and/or recommending medication to treat health problems that were not minor ailments, representing behaviors which may have legal implications and negative clinical results. Conclusion: In order to change this scenario, besides being essential for the community pharmacist to know and comply with the sanitary and professional laws of the profession, it is also important to develop competences related to evidence-based clinical practice and clinical services